Finance and Development, March 2003. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2003)
This paper analyzes why the Middle East and North Africa (MENA) region has lagged in growth and globalization. Despite attempts to spur recovery and initiate structural reforms, many countries in the region remain on a slow growth path, effectively sidelined from globalization and the benefits of closer economic integration with the rest of the world. The benefits from oil failed to generate a sustained growth dynamic or bring about greater regional economic integration. The paper highlights that the slowdown in economic reforms is a key factor for the economic depression in the MENA region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet